2020
DOI: 10.1038/s41366-020-0637-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between socioeconomic factors and weight loss 5 years after gastric bypass surgery

Abstract: Introduction Patients with low socioeconomic status have been reported to have poorer outcome than those with a high socioeconomic status after several types of surgery. The influence of socioeconomic factors on weight loss after bariatric surgery remains unclear. The aim of the present study was to evaluate the association between socioeconomic factors and postoperative weight loss. Materials and methods This was a retrospective, nationwide cohort study with 5-year follow-up data for 13,275 patients operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…In order to identify patients that are at risk of developing nonresponse, multiple factors have been investigated and so far, a pattern of an older age, a higher preoperative BMI, the presence of comorbidities, and behavioral and psychosocial factors have been shown to predict non-response [8,24,[31][32][33]. The current study showed male gender and preoperative hypertension increased the risk of non-response.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In order to identify patients that are at risk of developing nonresponse, multiple factors have been investigated and so far, a pattern of an older age, a higher preoperative BMI, the presence of comorbidities, and behavioral and psychosocial factors have been shown to predict non-response [8,24,[31][32][33]. The current study showed male gender and preoperative hypertension increased the risk of non-response.…”
Section: Discussionmentioning
confidence: 63%
“…This is CSA = circular-stapled anastomosis, LSA = linear-stapled anastomosis, TWL = total weight loss 1 Defined as successful weight loss (≥20% total body weight loss) within 1.5 years after surgery 2 Defined as significant weight regain (≥20% of a patients' lost weight) after initial successful weight loss (≥20% total body weight loss) 2 years after surgery 3 The total amount of patients included in the CSA group was 881 patients. The total amount of patients included in the LSA group was 11,587 patients [32].…”
Section: Discussionmentioning
confidence: 99%
“… 18 Previous studies have reported lower weight loss and improvement in health-related quality of life, as well as higher loss to follow-up after bariatric surgery for patients living in larger cities. 19 20 28 While part of these findings may be explained by the chronic stress and higher cortisol levels of urban life, as well as the higher availability of energy-dense food, the cause of these negative associations remains largely unknown. 29 However, low socioeconomic status and income are associated with poor health literacy, factors known to influence postoperative recovery and treatment compliance.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recent studies have also reported an association between several socioeconomic factors and the risk for complications, as well as the effect on weight loss and improvements in health-related quality of life after bariatric surgery. [18][19][20] However, the effect of socioeconomic factors on remission rates of T2D after bariatric surgery remains unknown.…”
mentioning
confidence: 99%
“…Additionally, Cadena-Obando et al found that lacking a fulltime job pre-surgery was a negative predictor for achieving successful weight loss (≥50%excess body weight loss) one year after various bariatric procedures [ 19 ]. Only the study by Stenberg et al reported long-term results and these results are in contrast to the abovementioned studies, as the authors found that pre-surgical employment as a professional or technician is independently associated with a lower %total weight loss (TWL) five years after Roux-en-Y gastric bypass (RYGB) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%